EVALUATION OF LOCAL IDENTITY FOOD IN THE DEVELOPMENT OF GASTRONOMIC TOURISM IN REZEKNE CITY AND COUNTY - Litavniece, Lienīte; Silicka, Inese (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The number of tourists increases every year, and it is necessary to improve the quality and quantity of tourism products. The importance of gastronomic tourism in today’s society and the necessity of its development in regions are determined by the market rules and principles. Developing gastronomic tourism in Latgale region will introduce competitive products in the border area of Latvia and will decrease the effect of being a remote part of the country; also, infrastructure will be improved in its counties that would contribute to the development of the region in the future. The aim of this paper: to evaluate local identity food in the development of gastronomic tourism in Rezekne city and county.